2019
DOI: 10.1002/jimd.12045
|View full text |Cite
|
Sign up to set email alerts
|

The genotypic spectrum of ALDH7A1 mutations resulting in pyridoxine dependent epilepsy: A common epileptic encephalopathy

Abstract: Pyridoxine dependent epilepsy (PDE) is a treatable epileptic encephalopathy characterized by a positive response to pharmacologic doses of pyridoxine. Despite seizure control, at least 75% of individuals have intellectual disability and developmental delay. Current treatment paradigms have resulted in improved cognitive outcomes emphasizing the importance of an early diagnosis. As genetic testing is increasingly accepted as first tier testing for epileptic encephalopathies, we aimed to provide a comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 33 publications
1
44
2
Order By: Relevance
“…Among them, 15 ALDH7A1 variants and three PLPBP variants were unreported previously. In a review of the literature, p. E427Q was the most common mutation presenting in 26 per cent of all alleles . This ‘hot spots’ mutation accounted for only 5 per cent in our study, but p. Y516C (16%), IVS11+1G>A (15%), and p. Y345C (13%) had high frequency.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Among them, 15 ALDH7A1 variants and three PLPBP variants were unreported previously. In a review of the literature, p. E427Q was the most common mutation presenting in 26 per cent of all alleles . This ‘hot spots’ mutation accounted for only 5 per cent in our study, but p. Y516C (16%), IVS11+1G>A (15%), and p. Y345C (13%) had high frequency.…”
Section: Discussioncontrasting
confidence: 45%
“…van Karnebeek et al focused on six cases with atypical manifestations among 266 cases reported in 49 articles. Coughlin et al reviewed the genetics of 185 cases from previous reports. Therefore, this study involved the largest cohort of patients with PDE in a single centre reported to date, with analysis of both clinical and genetic features.…”
Section: Discussionmentioning
confidence: 99%
“…Coughlin et al have recently published a comprehensive overview of 165 known ALDH7A1 pathogenic variants which includes the genotypes of 185 individuals. It is estimated that the carrier frequency of ALDH7A1 mutations is 1:127 and that the estimated incidence of ALDH7A1 deficiency is 1:64 352 live births …”
Section: Deficiency Of Aldh7a1mentioning
confidence: 99%
“…Seizures of patients with ALDH7A1 deficiency are well controlled on pyridoxine monotherapy in about 90% of cases, however, at least 75% of children have intellectual disability (ID) and developmental delay (DD). The degree to which they have ID/DD does not correlate with treatment delay, pretreatment symptomatic interval, or duration taken to achieve seizure control . Two add‐on treatment options have been trialed in relatively small numbers of patients.…”
Section: Deficiency Of Aldh7a1mentioning
confidence: 99%
“…Certain mutations in the ALDH7A1 gene cause pyridoxine‐dependent epilepsy (PDE), an autosomal recessive metabolic disease characterized by seizures and in some cases intellectual disability . The estimated carrier frequency of ALDH7A1 mutations is 1 : 127, and the estimated incidence of ALDH7A1 deficiency is 1 : 64 352 births . The molecular basis of PDE is a decrease in the ubiquitous enzyme cofactor pyridoxal 5′‐phosphate (PLP) caused by Knoevenagel condensation of PLP with Δ 1 ‐piperideine‐6‐carboxylic acid (P6C), the cyclized form of AASAL (Fig.…”
Section: Introductionmentioning
confidence: 99%